2009
DOI: 10.1159/000230693
|View full text |Cite
|
Sign up to set email alerts
|

Report of Negative Diffusion-Weighted MR Imaging during Tumor Resections Using Intraoperative MRI

Abstract: Intraoperative MR imaging allows surgeons to continually assess the extent of resection of a tumor and other potential complications. Diffusion-weighted MR imaging (DWI) is a very important diagnostic tool for the early detection of ischemic injury to the brain. Ischemic changes could potentially result in the development of infarction and neurological deficits during brain tumor resections; however, the incidence and importance of negative DWI is poorly understood. Here, we describe 3 cases of negative DWI du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…In the intraoperative setting, however, the occurrence of false-negative DWI imaging in ioMRI is clearly underreported and includes only reports of single cases 16 , 17 . Prabhu et al 17 presented three cases with false-negative DWI in ioMRI during tumor resection, although in one patient additional resection was performed after intraoperative resection control, and no information was provided about the other two cases regarding extended resection. In our current report we explicitly filtered cases where no further resection was performed after ioMRI in order to prevent accidental inclusion of new infarcts induced surgically after ioMRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the intraoperative setting, however, the occurrence of false-negative DWI imaging in ioMRI is clearly underreported and includes only reports of single cases 16 , 17 . Prabhu et al 17 presented three cases with false-negative DWI in ioMRI during tumor resection, although in one patient additional resection was performed after intraoperative resection control, and no information was provided about the other two cases regarding extended resection. In our current report we explicitly filtered cases where no further resection was performed after ioMRI in order to prevent accidental inclusion of new infarcts induced surgically after ioMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Various possible explanations for the phenomenon of false-negative DWI findings have been postulated. A focal reduction in cerebral blood flow (CBF) below a threshold critical for neuronal function but still sufficient for proper diffusion was suggested 17 , 31 , 32 . Numerous studies have tried to determine the critical CBF threshold for survival of the penumbra in focal ischemia 31 , 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although DWI images were previously described to reach a high sensitivity and specificity to detect ischemic brain lesions [5], falsenegative reports of DWI sequences are present. This phenomenon of false-negative or underestimated infarcts on MRI is not well described and poorly understood, especially in ioMRI [10,15,18] and also in hyperacute stroke imaging [8,[14][15][16]. Possible explanations might be that ioMRI occurs too early to detect hyperacute infarcts or that vasospasms contribute to delayed infarct development without further tissue manipulation by the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The use of multimodal neuroradiologic imaging in combination with highly technologic analyses is useful for making neurosurgical procedures possible, especially in noncircumscribed brain tumors such as glioma (Wakabayashi et al, 2009). Diffusion-weighted imaging (DWI) is an essential diagnostic tool in the postoperative setting for the early detection of ischemic brain injury that could potentially result in infarction and development of neurologic deficits during surgical resection (Prabhu, Levine, Rao, Shah, & Weinberg, 2009). Several studies have shown that postoperative ischemic brain injury is common in glioma surgical resections and best detected by DWI showing diffusion restriction.…”
Section: J Adv Pract Oncolmentioning
confidence: 99%